Prospects of Arbuscular Mycorrhizal Fungi Utilization in Production of Allium Plants - Golubkina, Nadezhda (Plants (Basel), 2020)
The need to improve crop yield and quality, decrease the level of mineral fertilizers and pesticides/herbicides supply, and increase plants’ immunity are important topics of agriculture in the 21st century. In this respect, arbuscular mycorrhizal fungi (AMF) may be considered as a crucial tool in the development of a modern environmentally friendly agriculture. The efficiency of AMF application is connected to genetic peculiarities of plant and AMF species, soil characteristics and environmental factors, including biotic and abiotic stresses, temperature, and precipitation. Among vegetable crops, Allium species are particularly reactive to soil mycorrhiza, due to their less expanded root apparatus surface compared to most other species. Moreover, Allium crops are economically important and able to synthesize powerful anti-carcinogen compounds, such as selenomethyl selenocysteine and gamma-glutamyl selenomethyl selenocysteine, which highlights the importance of the present detailed discussion about the AMF use prospects to enhance Allium plant growth and development. This review reports the available information describing the AMF effects on the seasonal, inter-, and intra-species variations of yield, biochemical characteristics, and mineral composition of Allium species, with a special focus on the selenium accumulation both in ordinary conditions and under selenium supply.